'It brings the lads together': a critical exploration of older men's experiences of a weight management programme delivered through a Healthy Stadia project. Issue 2 (1st February 2017) - Lozano-Sufrategui, Lorena; Pringle, Andy; Carless, David; McKenna, Jim
Abstract: Older men whose weight is considered unhealthy may experience particular barriers that can restrict their adoption of health improvement interventions. Despite promising findings recommending the use of sports settings to facilitate health promotion with men, little evidence has addressed older men's health needs for, or experiences of, these settings. Using a qualitative methodology, this study explored the experiences of 14 ageing men attending a football-led weight management programme delivered at a community sports setting. The thematic analysis of semi-structured interviews elucidates important insights regarding the provision of sports-led health improvement interventions for this population. Men especially valued the opportunity to play sports and do physical activity in an environment that promotes 'inclusive' competition and caring interpersonal relationships. Implicit in the findings is the key role of practitioners in promoting social engagement. We conclude the paper with key practical implications of this research.